PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING TERHADAP AKTIVITAS DAN PRESTASI BELAJAR IPS SD - I Gusti Agung Ayu Lily Purnami; Lasmawan, I Wayan; Kertih, I Wayan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In primary school social studies education, the low interest of students in this subject presents a challenge for educators to apply teaching strategies that can enhance students' motivation to learn. This study aims to examine the effect of the Contextual Teaching and Learning (CTL) model on students' learning activities and academic performance in grade IV at SD Negeri 1 Manikyang. The research design is a quasi-experiment with a quantitative approach, utilizing a posttest-only control group design. The subjects of the study consisted of two classes: the experimental class, which applied the CTL model, and the control class, which used conventional teaching methods. Data were collected through the measurement of learning activities and academic performance using questionnaires and tests. The results showed that the CTL model had a positive and significant effect on students' learning activities and academic performance. The average learning activity score in the experimental class (77) was higher compared to the control class (72), while the average academic performance score in the experimental class (79) was also higher compared to the control class (76). The results of the MANOVA statistical test indicated that the effect of the CTL model on both variables was significant (p < 0.05). Therefore, it can be concluded that the implementation of the CTL model can significantly improve students' learning activities and academic performance. This study suggests that the CTL model should be more widely applied in teaching to enhance student engagement and learning outcomes.